Health Content of Afghan Media - Najafizada, Said Ahmad Maisam (Université d'Ottawa / University of Ottawa, 2011)
Television has developed dramatically over the past six years in Afghanistan with a potential for providing extensive health information to its viewers, yet little is known about the coverage of health issues on Afghan television. Using the theories of agenda-setting and framing, and social norms approach this study explored what health-related topics were covered, how they were covered, and what sociocultural practices were broadcasted by the major Afghan private, national televisions. The study used a sample of six constructed weeks in 2010 of two leading private, national television networks. Firstly, the study found that priority health problems such as maternal and child health, communicable disease and mental health received very less coverage. Secondly, however, individual-level and societal-level causes were blamed equally for the health problems; individual behaviour solutions were the favourite choice of the media, turning a blind eye to government weakness and organizational solutions. Thirdly, self-prescription, religious and traditional health seeking behaviour, and gender inequity were routine practices reflected on television. As the first content analyses of the coverage of health-related issues in Afghanistan, the study provides public health professions, the Afghan media and policy makers a broad picture of health information available to the public on the leading Afghan television stations.
Keywords: Afghanistan; Health; Media; Social norms